2014
DOI: 10.1371/journal.pone.0090181
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Approach to Screening of Potential Diagnostic and Therapeutic Targets for Laryngeal Carcinoma

Abstract: To discover candidate biomarkers for diagnosis and detection of human laryngeal carcinoma and explore possible mechanisms of this cancer carcinogenesis, two-dimensional strong cation-exchange/reversed-phase nano-scale liquid chromatography/mass spectrometry analysis was used to identify differentially expressed proteins between the laryngeal carcinoma tissue and the adjacent normal tissue. As a result, 281 proteins with significant difference in expression were identified, and four differential proteins, Profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
3
24
2
Order By: Relevance
“…3C and SI Appendix, Fig. S4A) and notably, 6 of these genes (ARNTL, CEACAM7, GATA2, HHEX, KLRG1, and OGN) have been reported to possess tumor suppressor activity (18)(19)(20)(21)(22)(23). qPCR analysis of the 10 genes in three additional breast cancer cell lines revealed that their expression was down-regulated in hypoxia in a similar manner to that observed in MCF7 breast cancer cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 59%
“…3C and SI Appendix, Fig. S4A) and notably, 6 of these genes (ARNTL, CEACAM7, GATA2, HHEX, KLRG1, and OGN) have been reported to possess tumor suppressor activity (18)(19)(20)(21)(22)(23). qPCR analysis of the 10 genes in three additional breast cancer cell lines revealed that their expression was down-regulated in hypoxia in a similar manner to that observed in MCF7 breast cancer cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 59%
“…This study also showed a reduction or absence of OGN expression in different tumors, such as adenocarcinomas of the breast, colon, lung, ovary, prostate, and pancreas and in different cancer cell lines, where p53 is frequently mutated or inactivated (19). Moreover, many other studies have shown decreased OGN expression in different cancers, such as human gastric cancer (68), colorectal adenoma (69), squamous cervical and squamous vaginal cancer (70), invasive ductal breast carcinoma (71), laryngeal carcinoma (72), and mouse and human thyroid tumors (73), when compared to its expression in control tissues. The latter study even showed a progressive decrease in OGN expression compared with that in normal tissue, in follicular adenoma progressing to aggressive follicular adenoma, indicating that a decrease in OGN expression parallels thyroid tumor progression.…”
Section: Ogn In Diseasementioning
confidence: 99%
“…Mimecan (or Osteoglycin, OGN), is a secretory protein that belongs to a family of small leucine rich proteoglycan (SLRPs). It has been found in several cancer cell lines, although its physiological function has not been completely understood [18, 19], being abundant in bone matrix, cartilage cells, and connective tissues; it is also important for collagen fibrillogenesis, cellular growth, differentiation and migration [20] and it has been involved in the pathogenesis of different cancers such as colorectal [21], laryngeal carcinoma [19] and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%